Effects and Anti-rotation Stabilization of the Non-bridging External Fixation for Pronation-Abduction Stage III Ankle Fracture: A Cadaveric Study. (10th May 2021) - Chen, Yili; Huang, Xiaoyu; Cheng, Yongzhong; Xu, Jingjing; Chen, Yang; Zhang, Qi; Wen, Jianmin
Abstract : Objective . This study is aimed at providing a nonbridging external fixation technique with pinning fixation for the pronation-abduction stage III ankle fracture. The secondary purpose was to evaluate its effect on anatomic reduction and fracture fragment stability against cadaveric models' rotation. Method . A paired design study was conducted using 14 pairs of the cadaveric model which had been modeled for pronation-abduction stage III ankle fracture. One fracture model from each pair was randomly allocated to receive an open reduction and internal fixation, while the other was reduced and stabilized with the external fixation technique. After the surgery, the antirotational stability tests were performed with external rotation torques of 10 nm, 15 nm, and 20 nm applied, respectively. The postoperation reduction rate and ankle parameters were recorded in anteroposterior and lateral radiographs before and after the antirotational stability experiment. Result . The outcomes were assessed according to Burwell-Charnley's radiographic criteria of reduction. It showed no statistically significant differences in reduction between the two groups (P < 0.05 ). The displacement of lateral fragment following a reduction in the external fixation group was significantly larger than that of the internal fixation group (3.14 ± 0.56 vs. 1.49 ± 0.39, P < 0.05 ). After applying rotational torques of 10 nm, 15 nm, and 20 nm, the results of other parameters showed no significant differences between the two groups. Conclusion . This nonbridging external fixation method with pin fixation of fracture fragments might have the same effect as that of internal fixation on the reduction rate of pronation-abduction stage III ankle fracture.